2017
DOI: 10.1016/j.firesaf.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural response of cross-laminated timber compression elements exposed to fire

Abstract: A set of novel structural fire tests on axially loaded cross-laminated timber (CLT) compression elements (walls), locally exposed to thermal radiation sufficient to cause sustained flaming combustion, are presented and discussed. Test specimens were subjected to a sustained compressive load, equivalent to 10 % or 20 % of their nominal ambient axial compressive capacity. The walls were then locally exposed to a nominal constant incident heat flux of 50 kW/m 2 over their mid height area until failure occurred. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 19 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…These results agree with the literature. Wiesner et al [50] exposed timber walls to a constant heat flux and found zero-strength layers between 15 and 22 mm. Schmid et al exposed timber to the standard fire and found zero-strength layers of up 19 mm.…”
Section: Discussion On Zero-strength Layermentioning
confidence: 99%
“…These results agree with the literature. Wiesner et al [50] exposed timber walls to a constant heat flux and found zero-strength layers between 15 and 22 mm. Schmid et al exposed timber to the standard fire and found zero-strength layers of up 19 mm.…”
Section: Discussion On Zero-strength Layermentioning
confidence: 99%
“…However, it must be reiterated that the RCSM method, in its current form, was not developed, and should not be used, for CLT. Previous researchers have already demonstrated that application of the RCSM to CLT is likely to result in unsafe capacity predictions [37][38][39]. It is expected that future versions of the Eurocode will suggest modifications to the charring rates and the zero strength layers to attempt to provide more conservative simplified design solutions for CLT and other engineered timber products.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, CLT was developed in Austria, Germany and Switzerland. The advantages of CLT include shorter building time and a high strength ratio [1]. CLT beams are composed of wood layers, arranged and glued crosswise as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%